KEDUDUKAN BARANG BUKTI DALAM PERKARA PIDANA DITINJAU BERDASARKAN KITAB UNDANG-UNDANG HUKUM ACARA PIDANA - Julius Bernat Hasibuan (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACTIn the Criminal Procedure Code, the evidence is not regulated in it but in the Criminal Procedure Code, the term evidence, also known as the term evidence, it appears that the evidence is not mentioned as included in one of the valid evidences. In other words, evidence is not a proof, questions can arise from here regarding the position of "evidence". Based on this description, the main problems in this paper are: (1) How the position of the evidence in the process of proving criminal cases according to the Criminal Procedure Code and (2) Is the Evidence a basis for proving a crime according to the Criminal Procedure Code. The approach to the problem used is normative juridical, legislative approach and co-conceptual approach. Collection of materials used are primary, secondary and tertiary data, collection of materials and processing of materials with literature. In this study, it will be analyzed using qualitative normative methods with deductive logic, namely thinking with general things that lead to specific things. The evidence basically can be used to declare an error in a criminal act, with a note that the evidence used as supporting evidence is valid as stipulated in the Criminal Procedure Code, because basically as long as the evidence is an item used to commit a criminal act , or an item is a result of a criminal act, the evidence is also supported by evidence. As for the author's suggestion in the changes to the KUHAP in the future, it should be one of the things that deserves to be implemented in its change is a clearer arrangement related to the position of evidence, as part of the evidentiary instrument in a criminal case. .Keywords: Evidence Item, Evidence Tool, Evidence and KUHAP.